Efektivitas Program Rumah-Kaca sebagai Upaya Peningkatan Ketahanan Pangan Masyarakat Desa Hanura Kecamatan Teluk Pandan Kabupaten Pesawaran - Izzul Fatchu Reza; Sarah Putri Andriani (Inovasi Pembangunan : Jurnal Kelitbangan, 2017)
As time passes, people in Hanura village can not produce their own food independently to meet their daily needs. This is because the majority of Hanura people work as non-farmers and market presence makes it easier for them to gain access to meet their daily needs. Therefore, the Hanura village government innovated by implementing the Greenhouse Program to improve people's food security by creating public awareness to produce food independently. The achievement of the Greenhouse Program as a learning media for movement and food production is self-reliant to the community. This makes the researcher curious to know how far the effectiveness of Green House Program as an effort to increase food security of community in Hanura village, Teluk Pandan Sub-district, Pesawaran Regency. This research is a qualitative research. Interview techniques, observation and documentation are administrated as data collection techniques research. The results show that the Greenhouse Program in improving the food security of Hanura villagers has not been effective because there is a lack of human resources that can follow the Greenhouse Program and the amount of food output in the Greenhouse Program has not been adequate for the overall needs of the Hanura villagers. Implementation of the Hanura Village Greenhouse Program has constrained the lack of public awareness to take part, the climate that inhibits the growth of plants in the Greenhouse and many local merchants are free to sell instant foods that are contrary to the purpose of the Greenhouse Program.